Stigma among primary care providers: characterizing attitudes and behaviors in the care of people with chronic hepatitis in the Philippines - Naeema Hopkins-Kotb; Jhaki Mendoza; Manu Gaspar; Martin Fernandez; Jae-Ann Sumalo; Timothy Mercado; Jovein Alcantara; Joshua Bartolome; Diana Rose de Silva; Janus P. Ong; Todd M. Pollack; David B. Duong; et al. (BMC Primary Care)
Abstract Background Stigma is a key barrier to compassionate primary health care delivery and people-centered care (PCC), but is understudied among primary care providers (PCPs). Hepatitis B and C have a significant burden of disease in the Philippines, where there is limited awareness of and access to screening and treatment. Patient-reported stigma has been identified as a significant barrier to hepatitis care in the Philippines, but PCP stigma-related attitudes and behaviors have not been explored in this context. Methods In this study, we assessed primary PCP-reported stigma-related attitudes and behaviors toward patients with hepatitis B and C. We surveyed primary PCPs in Tarlac, Philippines working within a network of healthcare facilities that have been part of an initiative to decentralize hepatitis care to the primary care level and prioritize PCC. Results We found that PCPs’ self-reported attitudes toward patients with hepatitis B and C reflect a strong sense of responsibility to provide care, and comfort with sensitive history-taking, but also pervasive attitudes of pity and blame. PCPs’ self-reported behaviors showed commitment to providing equal care, but variation in infection control practices suggesting misconceptions about transmission risk. Conclusions Our results provide essential insight into PCPs’ stigma-related attitudes and behaviors that will serve as a baseline for future comparison with patient-reported experiences. These findings underscore the critical role of primary care in addressing stigma and improving hepatitis care in the Philippines, highlighting the importance of training, resource allocation, and people-centered care strategies.